Complete Resolution of Hemodialysis-induced Pseudoporphyria after Renal Transplantation - Prodip Kumar Doley; Oyik Tamut; Manjuri Sharma; Gayatri Pegu (Indian Journal of Transplantation)
Bullous dermatoses in end-stage renal disease are not an uncommon entity. A high index of clinical suspicion is essential for the proper diagnosis of rare dermatological diseases in chronic kidney disease patients. Pseudoporphyria (PP) should consider in differential diagnosis of bullous dermatoses in patients on Maintenance hemodialysis (MHD). PP is a photo-distributed bullous disorder with clinical and histologic features of porphyria cutanea tarda (PCT) but without accompanying biochemical porphyrin abnormalities. PP is a blistering disease with skin fragility and shallow scarring that clinically and histopathologically closely resembles PCT. The two conditions can be distinguished by porphyrin levels that typically are elevated in PCT, but not or only slightly in PP. PP can be induced by various medications (e.g. nonsteroidal anti-inflammatory drugs, antibiotics, diuretics, and retinoids), intense ultraviolet (A) exposure, or hemodialysis. Treatment of hemodialysis-associated PP is not yet standardized. Here, we report a case of pseudoporphyria in a patient on maintenance hemodialysis, refractory to the conventional treatment, and who subsequently underwent successful renal transplantation with full resolution of skin lesions within a month.